(untitled) (Scottish Archaeological Internet Reports, 2004)
An outline of the circumstances of discovery, methodology and a brief summary of the finds. Despite the disturbed nature of the site and the brief duration of the archaeological work, Camas Daraich is interesting because it falls within a geographical area of ongoing Mesolithic research and provides an important link between the island of Rhum and the Inner Sound to the north.